HUBUNGAN POWER OTOT LENGAN DAN BAHU DAN KELENTUKAN DENGAN HASIL TOLAK PELURU GAYA O’BRIEN PADA ATLET PUTRA PPLP RIAU TAHUN 2018 - Yati, Suparni; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This reseach aims to find out wheter there is a correlation of arm and shoulder muscle power and flexibility with the result of o’brien shot put style in Riau PPLP athletes in 2018, the form of this sudy was correlation research, the population in this study were athletes PPLP Riau athletes numbered 12 people. The first analysis in the calculation of the correlation of arm and shoulder muscle power between X1 and Y, where rtable at sig-nificant level α (0,05) = 0.602 mens rresult (0.747)> rtable (0,602), which means the hypothe-sis is accepted and there is a strong correlation between correlation of arm and shoulder muscle power with the result of o’brien shot put style in Riau PPLP athletes PPLP Riau, a second analysis of flexibility (X2) with the result of o’brien shot put style (Y), where rtable at significant level α (0,05) = 0.602 means rresult (0,764)> rtable (0,602), which means the hy-pothesis is accepted and there is a strong correlations between flexibility with the result of o’brien shot put style in Riau PPLP athletes in 2018 , the third analysis, correlation of arm and shoulder muscle power (X1) and flexibility (X2) with the result of o’brien shot put style (Y) was obtained, which rtable at significant level α (0,05) = 0.602 , means rresult (0.706)> rtable (0,602). Then it can be concluded that the relationship between (X1) and (X2) premises Y or the correlation between of arm and shoulder muscle power and flexibility with the result of o’brien shot put style are significant. Therefore that the result of o’brien shot put style in Riau PPLP athletes in 2018 predicted by shoulder muscle power and flexibility.Keywords: arm and shoulder muscle power, flexibility, the result of o’brien shot put style